Treino neuromuscular e fortalecimento muscular em pacientes com síndrome da dor femoropatelar: ensaio clínico cego e aleatorizado - Rabelo, Nayra Deise dos Anjos (2014)
Patellofemoral pain syndrome (PFPS) is a common complaint, especially in women. The hip muscles strengthening is an effective technique for the treatment of this disorder. In addition, the neuromuscular training has received attention as a therapeutic tool, but results in individuals with PFPS are still very evident and inconclusive. Therefore, the aim of this study was to compare the effects of a neuromuscular training program of the trunk and lower limbs associated with the hip and knee muscles strengthening in women with PFPS with a program that involves the isolated strengthening of those muscles. Thirty-four women aged 18 to 35 years with a clinical diagnosis of PFPS were randomized into two groups: Strengthening Group (SG) and Neuromuscular Group (NMG). Patients underwent 12 sessions of the strengthening (Knee extensors, hip abductor and hip external rotator) and the NMG, associated with this, received the balance, coordination and control of the lower limb training. Because of the nature of the study, we chose to report now, only the results of force and kinematics, since the clinical analysis is still in progress. Thus, the effects of treatment on muscle strength and kinematics were calculated using paired t test for parametric measures and the Friedman test with post hoc, for nonparametric measures. At the end of 4 weeks of treatment, significantly increased the strength of the hip abductor muscles (percentage of improvement from 20.7% to 19% for SG and NMG), hip external rotators (percentage of improvement of 18.2% was observed for SG and 17% for NMG) and knee extensors (percentage of improvement from 19.7% to 16.2% for SG and NMG) in both groups, and effectively reduce the range of motion of hip adduction in the voluntary NMG. We conclude that both programs proposed treatment promoted increased strength of the muscles evaluated, but only the associated neuromuscular training to strength training was able to effectively create change in kinematics, real improvement in hip adduction.